Somewhere between heaven and earth - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Modelling Soil-Biosphere Interactions. C Müller, Department of Applied Microbiology, Justus-Liebig University, Germany. 1999. 360 pp. ISBN 0851993532. £49.95 81.95 CAB International (CABI) Wallingford, Oxfordshire OX10 8DE, UK. Fax: +44 149